Development and application of a biotic ligand model for predicting the chronic toxicity of dissolved and precipitated aluminum to aquatic organisms. (28th December 2017) - Santore, Robert C.; Ryan, Adam C.; Kroglund, Frode; Rodriguez, Patricio H.; Stubblefield, William A.; Cardwell, Allison S.; Adams, William J.; Nordheim, Eirik
Abstract: Aluminum (Al) toxicity to aquatic organisms is strongly affected by water chemistry. Toxicity‐modifying factors such as pH, dissolved organic carbon (DOC), hardness, and temperature have a large impact on the bioavailability and toxicity of Al to aquatic organisms. The importance of water chemistry on the bioavailability and toxicity of Al suggests that interactions between Al and chemical constituents in exposures to aquatic organisms can affect the form and reactivity of Al, thereby altering the extent to which it interacts with biological membranes. These types of interactions have previously been observed in the toxicity data for other metals, which have been well described by the biotic ligand model (BLM) framework. In BLM applications to other metals (including cadmium, cobalt, copper, lead, nickel, silver, and zinc), these interactions have focused on dissolved metal. A review of Al toxicity data shows that concentrations of Al that cause toxicity are frequently in excess of solubility limitations. Aluminum solubility is strongly pH dependent, with a solubility minimum near pH 6 and increasing at both lower and higher pH values. For the Al BLM, the mechanistic framework has been extended to consider toxicity resulting from a combination of dissolved and precipitated Al to recognize the solubility limitation. The resulting model can effectively predict toxicity to fish, invertebrates, and algae over a wide range of conditions. Environ Toxicol Chem 2018;37:70–79. © 2017 SETAC